2022
DOI: 10.1088/1674-1056/ac3648
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the transition properties of AlF

Abstract: Potential energy curves of the X1Σ+ and A1Π states of the AlF molecule are studied through the combination of the multi-reference configuration interaction (MRCI) approach and Davidson corrections (MRCI+Q). The AWCV5Z basis set is employed in the calculations. The transition dipole moments (TDMs) of the A1Π ↔ X1Σ+ transition are explored based on the AWCV5Z basis set and (4, 2, 2, 0) active space. The Schrödinger equation is solved via the LEVEL 8.2 program, and the vibrational levels and rotational constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
2
2
1
Order By: Relevance
“…Our value of D e for A 1 Π state is in excellent agreement with the only result available in Ref. [23]. The MRCI + Q value of ω e x e = 5.70 cm −1 for A 1 Π state is very close to the experimental value of 5.99 cm −1 [31], while for a 3 Π (B 1 Σ) state, our value is larger by 1.53 cm −1 (1.17 cm −1 ) from the experimental data.…”
Section: Electronic Properties: Ground and Low-lying Excited Statessupporting
confidence: 91%
See 4 more Smart Citations
“…Our value of D e for A 1 Π state is in excellent agreement with the only result available in Ref. [23]. The MRCI + Q value of ω e x e = 5.70 cm −1 for A 1 Π state is very close to the experimental value of 5.99 cm −1 [31], while for a 3 Π (B 1 Σ) state, our value is larger by 1.53 cm −1 (1.17 cm −1 ) from the experimental data.…”
Section: Electronic Properties: Ground and Low-lying Excited Statessupporting
confidence: 91%
“…A very similar behaviour of PDM curve of this system has been reported in Ref. [23], though they have not mentioned about the usage of state -averaged procedure in their work. It has been observed that the values of PDMs are almost zero at the dissociation limit for all electronic states, which means that the molecule dissociates into its constituent neutral fragments.…”
Section: Electronic Properties: Ground and Low-lying Excited Statessupporting
confidence: 81%
See 3 more Smart Citations